Pengaruh Live Shopping, Influencer Marketing, dan Online Review terhadap Proses Pengambilan Keputusan Pembelian Brand Wardah pada Generasi Z - Anna Nurwalidaini; Dwi Indah Puspita Rini; Meli Agustin; Ripa Nuraini; Zaskia Dwi Aulia Putri Cahya (Yayasan Literasi Sains Indonesia, 2026)
The development of digital technology has changed consumer behavior in the purchasing decision-making process, especially in Generation Z, who tend to utilize various sources of digital information before purchasing products. This research aims to analyze the influence of live shopping, influencer marketing, and online reviews on the decision-making process of purchasing Wardah products in generation Z in Bandung City. This research uses quantitative shorts with a survey method. Data collection was carried out through the distribution of questionnaires to 100 selected respondents using the purposive sampling technique. Data analysis was carried out using IBM SPSS Statistics 27 through validity test, reliability, classical assumption, multiple linear regression, t test, F test, and determination coefficient. Research results show that live shopping, influencer marketing, and online review have a positive and significant effect on the purchase decision-making process. In addition, the three variables also have a significant effect simultaneously on the purchase decision-making process. Influencer marketing variable is the variable that has the most dominant influence compared to other variables. The value of the determination coefficient (R²) of 0.734 shows that 73.4% of the variation in the purchase decision-making process can be explained by live shopping, influencer marketing, and online review, while the remaining 26.6% is influenced by other factors outside the research model. The research results confirm that the synergy between live shopping, influencer marketing, and online review is able to increase the effectiveness of digital marketing and strengthen the purchase decision-making process for Generation Z consumers.